Medical device regulation in vascular ageing assessment: a VascAgeNet survey exploring knowledge and perception - Martina, Maria Raffaella; Park, Chloe; Alastruey, Jordi; Bruno, Rosa Maria; Climie, Rachel E; Dogan, Soner; Tuna, Bilge Guvenc; Jerončić, Ana; Manouchehri, Marjan; Panayiotou, Andrie G.; Tamarri, Silvia; Terentes-Printzios, Dimitrios; et al. (My University, 2024)
Regulation has a key role for medical devices throughout their lifecycle aiming to guarantee effectiveness and safety for users. Requirements of Regulation (EU) 2017/745 (MDR) have an impact on novel and previously approved systems. Identification of key stakeholders' needs can support effective implementation of MDR improving the translation to clinical practice of vascular ageing assessment. The aim of this work is to explore knowledge and perception of medical device regulatory framework in vascular ageing field.
Keywords: MDR; Medical device; regulation; survey; vascular ageing